Culture, bathing and hydrotherapy in labor: An exploratory descriptive pilot study. (September 2018) - Benfield, Rebecca; Heitkemper, Margaret M.; Newton, Edward R.
Highlights: Women who bathe, report relief of anxiety, menstrual and labor pain and promotion of mental and physical relaxation. Bathing is a self-care measure used by women and transmitted from generation to generation by female elders through the oral tradition. Assumptions that race or ethnicity precludes the use of bathing may be faulty. Bathing is a self-care measure used by women for dysmenorrhea. Abstract: Objective: Though bathing (hydrotherapy) is widely used during labor to decrease anxiety and pain and to promote relaxation, the influence of cultural beliefs about bathing by parturients is virtually unknown. This pilot study explored pregnant women's experiences of bathing, bathing in labor, and cultural beliefs about bathing. Design: An exploratory, descriptive design. Setting: Low risk obstetrical clinics. Participants: Healthy Hispanic, Black, White, American-Indian and Asian women ( N  = 41) at >37 weeks gestation. Methods: During a routine prenatal visit women responded to a brief openended questionnaire on the use of bathing. Data was captured using a modified ethnographic method involving observation and note taking with thematic analysis and quantification of percent response rates. Findings: Forty-six percent ( N  = 41) of women used bathing for purposes other than hygiene but only 4.9% ( N  = 41) of these women bathed during a previous labor. The women described bathing as relaxing, easing, calming, and efficacious for relief of menstrual cramps and labor contractions. Ten percent of women reported cultural beliefs about bathing. Conclusions: Women who bathe, report relief of anxiety, menstrual and labor pain and promotion of mental and physical relaxation. The findings do not support the view that bathing is associated with identifiable cultural beliefs; rather, they suggest that bathing is a self-care measure used by women. This practice is likely transmitted from generation to generation by female elders through the oral tradition. Assumptions that race or ethnicity precludes the use of bathing may be faulty. Cautionary instructions should be given to pregnant women who are <37 completed weeks of gestation, to avoid bathing for relief of cramping or contractions and to seek immediate health care evaluation. Study of culturally intact groups may uncover additional themes related to bathing in labor and as a self-care measure for dysmenorrhea.